2014
DOI: 10.1007/s11676-014-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Implications of crude oil pollution on natural regeneration of plant species in an oil-producing community in the Niger Delta Region of Nigeria

Abstract: The study evaluated the impact of crude oil pollution on natural regeneration of plant species in a major oil-producing community in the Niger Delta region of Nigeria. Three sites-unpolluted site (US), polluted and untreated site (PUS), and polluted and treated site (PTS)-were purposively chosen for the study. The seedling emergence method was used to evaluate soil seed banks in the various sites at two depths, 0 to 10 cm and 10 to 20 cm. Woody-plant species richness, abundance, and diversity were higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Gazelle activity and feces have been observed in the contaminated area during the field work, even in the area affected by the recent oil spill in 2014 (personal observation); thus, enough fertile Acacia seeds should have been available throughout. Inhibition of germination by crude oil or its compounds has been reported before (Adam and Duncan, 2002;Besalatpour et al, 2008;Chima and Vure, 2014), and, like in Evrona, some species showed higher vulnerability than others (Chaîneau et al, 1997). A third scenario-which fits the pattern observed with S. cyclophylla-is that seeds germinate but that seedling growth is inhibited, as was shown for Brassica napus L. and Trifolium repens L. (Besalatpour et al, 2008) and Hordeum vulgare L. (Li et al, 1997).…”
Section: Abundance and Size Distributionsupporting
confidence: 62%
See 2 more Smart Citations
“…Gazelle activity and feces have been observed in the contaminated area during the field work, even in the area affected by the recent oil spill in 2014 (personal observation); thus, enough fertile Acacia seeds should have been available throughout. Inhibition of germination by crude oil or its compounds has been reported before (Adam and Duncan, 2002;Besalatpour et al, 2008;Chima and Vure, 2014), and, like in Evrona, some species showed higher vulnerability than others (Chaîneau et al, 1997). A third scenario-which fits the pattern observed with S. cyclophylla-is that seeds germinate but that seedling growth is inhibited, as was shown for Brassica napus L. and Trifolium repens L. (Besalatpour et al, 2008) and Hordeum vulgare L. (Li et al, 1997).…”
Section: Abundance and Size Distributionsupporting
confidence: 62%
“…The similarity in composition of perennial plants between the oil-contaminated area and the reference areas suggests that the plant community has either not been affected by the oil spill or has managed to recover within the 40 yr subsequent to it. In contrast to this result, other scholars documented persistent (after 1 to 20 yr) changes in plant community composition as a consequence of contamination with petroleum hydrocarbons (Cowell, 1969;Hussein and Terry, 2002;Chima and Vure, 2014). The different result obtained from Evrona may be due to different site conditions or the long time period that has passed since the 1975 oil spill, which may have allowed plants to recover.…”
Section: Plant Compositionmentioning
confidence: 72%
See 1 more Smart Citation
“…It mainly occurs through oil spills, leaks, and accidents due to system failures, human errors, or negligence. The presence of crude oil in the environment can be hazardous to humans and has negative effects on the natural environment [1][2][3][4]. Petroleum hydrocarbons (PHCs) are compounds found in crude oil comprised of carbon and hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…High NDVVI values extracted from predsites following implementation of the best performing model contrasted with the very low NDVI values and suggest that the new index is more capable of detecting vegetation presence than the NDVI in oil polluted regions. Due to the adverse effect of oil pollution on vegetation (reduced growth [165][166][167] and increased mortality [168][169][170], the NDVVI designed to have maximum sensitivity to soil TPH, appears to be a more suitable index to measure vegetation characteristics because of its ability to detect even sparse areas of vegetative growth/presence. Furthermore, the NDVVI variants successfully predicted the diversity indices for the randomly selected sites from the satellite image of the study area.…”
Section: Discussionmentioning
confidence: 99%